THE RELATIONSHIP BETWEEN WORK-LIFE BALANCE AND PSYCHOLOGICAL WELL-BEING AMONG EMERGENCY DEPARTMENT NURSES IN HOSPITALS - Churnawan, Rizky Purnomo Adji; Anisa, Nur (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
This study examines the relationship between work-life balance and psychological well-being among nurses working in the Emergency Department (ED) at hospitals in the Bekasi region. The background of this research is based on the high workload and professional demands faced by ED nurses, which have the potential to impact their psychological well-being. The study aims to analyze the relationship between work-life balance and psychological well-being. The research method employed was non-probability sampling, involving 100 ED nurses as respondents. Data collection instruments consisted of questionnaires with work-life balance and psychological well-being scales that had been tested for validity and reliability.The data analysis results revealed a very strong positive relationship between work-life balance and psychological well-being (r = 0.877, p < 0.01). This indicates that an improvement in the balance between work and personal life correlates with an enhancement in psychological well-being. The discussion highlights that ED nurses who can maintain a balance between professional responsibilities and personal life tend to have better mental health, reducing stress and anxiety levels.In conclusion, this study emphasizes the importance of work-life balance in improving the psychological well-being of ED nurses. Therefore, it is recommended that hospitals consider the needs of nurses when formulating work policies, such as providing flexible working hours and social support, to enhance the well-being of healthcare professionals and the quality of services provided.